2018
DOI: 10.1155/2018/9694615
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Body Composition of Children at the Early School Age from Urban and Rural Area in Southwestern Poland

Abstract: The aim of the study was to compare the segmental body composition with the use of fat–fat-free (FFF) index in children at early school age, depending on sex and place of residence, with particular emphasis on urban and rural areas. The study consisted of 329 children aged 7.78 (SD = 0.88; mean age in years). The study group was divided according to the place of residence and sex. The height and body mass, Body Mass Index (BMI), segmental body composition (Tanita BC-418MA), and FFF were calculated. A more freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
(13 reference statements)
3
16
0
Order By: Relevance
“…In this study, boys have a lower percentage of adipose tissue than girls. This is consistent with the results of available research (McCarthy et al, 2006, Halasi et al, 2018Taylor et al, 1997;Chwałczyńska et al, 2018). Zhang et al (2015) analysed fatness in Tibetan children.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, boys have a lower percentage of adipose tissue than girls. This is consistent with the results of available research (McCarthy et al, 2006, Halasi et al, 2018Taylor et al, 1997;Chwałczyńska et al, 2018). Zhang et al (2015) analysed fatness in Tibetan children.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding Fat Free Mass (FFM) in our study, there is more in boys. This is also the case in the studies of Chwałczyńska et al (2018) and Sen & Mondal (2013). Also, Dencker et al (2007) found more Fat Free Mass (FFM) in boys (p <0.001).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations